Comparative study of packaging materials developed from fish and legume protein concentrates - Evmorfia Athanasopoulou; Angeliki Katsiroumpa; Chrysavgi Gardeli; Theofania Tsironi (Future Foods)
The environmental impact of food packaging, transportation and disposal are escalating, contributing significantly to global solid waste. There's an increasing focus by industry and research on seeking new sustainable solutions for waste valorization. This study investigates the isolation process of biopolymers from legumes (lentil) products and fish (gilthead seabream) waste, with the aim of producing composite films. The developed films were characterized for optical, mechanical and water barrier properties, hydrophobicity (via contact angle measurement), moisture content, water solubility, and biodegradability. Results indicated that lentil and fish protein concentrates may be effectively utilized to fabricate biodegradable packaging materials with adequate moisture barrier properties and excellent optical characteristics. The composite materials from lentil proteins and pectin had higher elongation at break compared to the respective value of the films produced using fish protein and gelatin (44.94 ± 2.81 % and 10.52 ± 1.21 %, respectively). Regarding the composite animal based film, the WVTR and WVP values were measured at 119.50 ± 2.90 g × s−1 × m−2 and 5.04±0.06 × 10−8 × g × m−1 × s-1×Pa−1, respectively. The composite plant based materials had higher WVTR and WVP (139.17 ± 8.01 g × s−1 × m−2 and 7.80 ± 0.91 × 10−8 × g × m−1 × s-1×Pa−1, respectively). The composite film of pectin and concentrated lentil protein exhibited hydrophobic behavior (contact angle 98.63 ± 3.78°), whereas for gelatin and concentrated fish protein films, the contact angle was determined as 57.37 ± 4.00°, indicating hydrophilic behavior. All produced films biodegraded in <20 days during burial test in soil with high relative humidity (80 %). The results of the study show the utilization of food industry potential waste for producing environmentally friendly packaging materials.